2001
DOI: 10.1074/jbc.m107737200
|View full text |Cite
|
Sign up to set email alerts
|

Phe71 Is Essential for Chaperone-like Function in αA-crystallin

Abstract: Experiments with mini-␣A-crystallin (KFVIFLD-VKHFSPEDLTVK) showed that Phe 71 in ␣A-crystallin could be essential for the chaperone-like action of the protein (Sharma, K. K., Kumar, R. S., Kumar, G. S., and Quinn, P. T. (2000) J. Biol. Chem. 275, 3767-3771). In the present study we replaced Phe 71 in rat ␣A-crystallin with Gly by site-directed mutagenesis and then compared the structural and functional properties of the mutant protein with the wild-type protein. There were no differences in molecular size or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 48 publications
5
48
0
Order By: Relevance
“…However, such binding caused a decrease in chaperone activity (42). Recent studies in ␣A-crystallin have suggested that factors other than hydrophobicity might also play important roles in the chaperone activity (45)(46)(47). The observation that the hydrophobicity is not the sole determinant of chaperone activity was also supported by our findings.…”
Section: Discussionsupporting
confidence: 78%
“…However, such binding caused a decrease in chaperone activity (42). Recent studies in ␣A-crystallin have suggested that factors other than hydrophobicity might also play important roles in the chaperone activity (45)(46)(47). The observation that the hydrophobicity is not the sole determinant of chaperone activity was also supported by our findings.…”
Section: Discussionsupporting
confidence: 78%
“…There are numerous instances where hydrophobicity could not be directly correlated to the chaperone-like activity of ␣A-and ␣B-crystallins. For instance, replacement of Phe-71 with Gly in ␣A-crystallin results in loss of chaperone activity despite an increase in surface hydrophobicity with no significant alterations in structure (26). In another study, calf lens ␣A-crystallin was found to be more hydrophobic but showed lower chaperone activity than ␣B-crystallin at room temperature (18).…”
Section: Resultsmentioning
confidence: 93%
“…The sequence of α-crystallin is broadly divided into N-terminal region consisting of about 60 residues, the α-crystallin domain consisting of about 80 -90 residues and a C-terminal tail consisting of 25 -30 residues [4,5,8,9]. Numerous studies done on -crystallinsubstrate interaction have implicated parts of the N-terminal region as substrate binding site [7,[10][11][12]. This region has also been reported to control the oligomeric size of the chaperone [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%